Silvicultura e percepção da paisagem no município de Cacequi/RS - Maass, Patrícia Arend (2013)
Since the beginnings of social organization in the land surface, men are concerned with ensuring their vital needs, which translates into different forms of appropriation of geographical space. Faced with this worry, the habit of observing nature to understand the phenomena of the Earth has become a constant in human life. The Geography has the important role of uncovering such phenomena and study the relationships of man's interference with natural processes, whose changes can lead to imbalance of the environment. Accordingly, this paper presents a study of the perception of residents Cacequi/RS with respect to the consequences of changes resulting from the implementation of forestry in the municipality considering the silvicultora activity as a potential factor configuration and reconfiguration of the landscape. It is a search that involves perception, based on the concept of intentionality of the John Searle, analyzing aspects of human cognition that are reflected in the way people relate to their environment. Methodologically, the research was developed from identification, through satellite images, of changes in the landscape resulting from silviculture. The identification of these areas allowed the selection of sites where interviews were conducted with the residents of urban and rural areas of the municipality. Interview data were organized for the interpretation of the results, seeking to highlight the different perceptions expressed by residents regarding the conformation of the landscape. Considering factors such as the features of the landscape, generation jobs and wealth for the city and the environmental impacts resulting from the implementation of forestry, the results obtained from this study reveal positive and negative perceptions among residents, with emphasis on the concern regarding the consequences of silviculture. It is understood, therefore, that the perception of the landscape is reflected incisively about the organization of geographical space.